The effect of particle sizes of steel slag as cement replacement in high strength concrete under elevated temperatures - Ho, Chia Min; Doh, Shu Ing; Chin, Siew Choo; Li, Xiaofeng (Elsevier, 2024)
This study investigates the impact of utilizing steel slag (SS) as a partial substitute for cement in high strength concrete (HSC) under high temperatures covering a range from 200 °C to 800 °C over a duration of 2 h. Two particle sizes of SS: 75 µm and 150 µm, were utilized as fine steel slag (FSS) and coarse steel slag (CSS). This study evaluates several physicochemical and compressive strengths of the HSC. After conducting the compressive strength, both residual compressive strength (RCS) and relative residual compressive strength (RRCS) were calculated. Scanning electron microscopy (SEM), Thermogravimetric analysis (TGA), and X-Ray Diffraction (XRD) analysis were carried out to analyze the physicochemical properties of HSC before and after subjected to elevated temperatures. The findings indicate an increase in the RCS of all specimens up to 400 °C. The replacement of FSS for cement enhances the compressive strength of HSC at ambient temperature, and FSS performs better than CSS up to 200 °C. However, beyond 400 °C, CSS exhibits a superior RRCS compared to FSS. XRD analysis confirms mineralogical changes in the HSC after exposure to fire, including the decomposition of C-S-H gel and the conversion of calcium hydroxide into calcium carbonate. The present study suggests that incorporating CSS in HSC has the potential to enhance its performance under high temperature conditions.